2019
DOI: 10.1111/ajo.13025
|View full text |Cite
|
Sign up to set email alerts
|

In overweight and obese women, fetal ultrasound biometry accurately predicts newborn measures

Abstract: Introduction The aim of this study was to evaluate the association between fetal ultrasound and newborn biometry and adiposity measures in the setting of maternal obesity. Material and Methods The study population involved 845 overweight or obese pregnant women, who participated in the Standard Care Group of the LIMIT randomised trial (ACTRN12607000161426, 9/03/2007). At 36 weeks gestation, fetal biometry, estimated fetal weight (EFW) and adiposity measures including mid‐thigh fat mass (MTFM), subscapular fat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 49 publications
1
3
1
Order By: Relevance
“…Although some have suggested that the accuracy of US EFW is negatively impacted by increasing maternal BMI, 14–16 in our experience, scan accuracy was not influenced by maternal BMI. This is consistent with more recent studies, 17–19 which have also demonstrated no statistically significant link. We also found that scan accuracy was not influenced by ethnicity, parity or gestational age at scan.…”
Section: Discussionsupporting
confidence: 93%
“…Although some have suggested that the accuracy of US EFW is negatively impacted by increasing maternal BMI, 14–16 in our experience, scan accuracy was not influenced by maternal BMI. This is consistent with more recent studies, 17–19 which have also demonstrated no statistically significant link. We also found that scan accuracy was not influenced by ethnicity, parity or gestational age at scan.…”
Section: Discussionsupporting
confidence: 93%
“…A recent Australian report suggested, in contrast to our findings, that a 36‐week ultrasound scan can accurately represent birthweight 19 . The difference may result from a different approach to the statistical analysis: our study used classification measurements including sensitivity, specificity, PPV and negative predictive value.…”
Section: Discussioncontrasting
confidence: 59%
“… 36 51 52 53 AFM measures taken during the third trimester have only variably been associated with birth weight and neonatal adiposity. 54 55 56 This suggests that fetal AFM measurements may not be the most reliable fetal subcutaneous tissue measurement for defining a fetal population at increased risk of being born LGA, and additional work on other fetal subcutaneous tissue measurements, and overall fetal body composition, are required.…”
Section: Discussionmentioning
confidence: 99%
“…With regards to fetal subcutaneous tissue thickness measurements, most interest in the literature has focused on abdominal fat mass measurements, and the utility of this measurement in predicting birth weight and risk of LGA infants (36,(51)(52)(53). Abdominal fat mass measures taken during the third trimester have only variably been associated with birth weight and neonatal adiposity (54)(55)(56). This suggests that fetal AFM measurements may not be the most reliable fetal subcutaneous tissue measurement for defining a fetal population at increased risk of being born LGA, and additional work on other fetal subcutaneous tissue measurements, and overall fetal body composition, are required.…”
Section: Accepted Manuscriptmentioning
confidence: 99%